Juridical Analysis of the Implementation of Artificial Insemination in Indonesia: Legal Status and Children's Rights in a Positive Legal Perspective - Priyatama, Sandra; Aliyah, Nelud Darajaatul; Mardikaningsih, Rahayu; Safira, Mirza Elmy; Issalillah, Fayola (Metromedia, 2022)
This study aims to analyze the implementation of artificial insemination in Indonesia based on Law Number 36 of 2009 concerning Health and evaluate the legal status and rights of children resulting from artificial insemination using sperm donors from a positive legal perspective. Using a normative juridical approach, this study utilizes secondary data from laws and regulations, legal journals, and academic literature. The results of the study show that the regulation regarding artificial insemination in Indonesia is still not comprehensive. Existing regulations focus more on the medical aspect, without providing legal certainty on the status of children resulting from artificial insemination, especially those involving sperm donors or surrogate mothers. These children often lose legal recognition which has an impact on the loss of civil rights, such as inheritance rights. The fatwa of the Indonesian Ulema Council also emphasized that this practice is contrary to religious norms, creating a dilemma for couples who need assisted reproductive technology. This study recommends the establishment of special regulations to accommodate the development of this technology, harmonization between legal and religious norms, and protection of the rights of children resulting from artificial insemination. Comprehensive regulations will provide legal certainty and reduce social conflicts that may arise.